Journal Closure - Journal of Infrastructure & Facility Asset Management (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
JOURNAL OF INFRASTRUCTURE & FACILITY ASSET MANAGEMENTVolume 1, Issue 1, March 2019 (e) ISSN 2656-8896 (p) ISSN 2656-890X